Intergenerational Impact of Violence Exposure: Emotional-Behavioural and School Difficulties in Children Aged 5–17 - Hashemi, Ladan; Fanslow, Janet; Gulliver, Pauline; McIntosh, Tracey (Frontiers in Psychiatry, 2022)
Background and objectives: The intergenerational impacts of parental exposure to violence during childhood and adulthood have largely been investigated separately. This limits our understanding of how cumulative violence exposure over a lifespan elevates the risk of subsequent generation’s maladjustment. To address this, we examined if parental exposure to violence during childhood and during adulthood was associated with increased emotional-behavioural and school difficulties among the children of these parents. Further, we examined if parental exposure to cumulative violence increased the odds of their children experiencing difficulties. Participants and setting: 705 participants (354 mothers and 351 fathers) from the 2019 New Zealand Family Violence Survey, a population-based study conducted in New Zealand between March 2017-March 2019. Methods: Multivariable logistic regressions were conducted to ascertain the impact of parental exposure to violence on children’s outcomes after adjustment for sociodemographic characteristics. The impact of parental cumulative violence exposure on children’s outcomes was also explored. Results: Findings indicated that children of parents who had histories of exposure to violence during childhood were at increased risk for experiencing emotional-behavioural or school difficulties. However, where parents reported a history of childhood abuse but not adult experience of violence, their children had similar odds of experiencing difficulties as the children of parents who had not been exposed to any violence in their lifetime. Children of parents who had been exposed to violence only during adulthood were at higher risk of experiencing emotional-behavioural difficulties compared with children of parents with no violence exposure. Children of parents with histories of exposure to violence during both childhood and adulthood had the highest prevalence of experiencing emotional/behavioural and school difficulties. Conclusion: These findings highlight the intergenerational impacts of violence exposure and the complex intersections between parents’ and children’s life experiences. Our findings suggest the need for violence prevention initiatives to foster the development of safe, stable and nurturing relationships and to expand services for parents already exposed to violence to build resilience and to break the inter-generational cycle of disadvantage.